1990
DOI: 10.3109/10408449009089864
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Effect of Lead in Occupationally Exposed Workers: A Critical Review

Abstract: In their discussion of field testing of health effects of environmental and industrial toxins, Gullion and Eckerman make the following observations which can be applied to the current literature survey: "The general inattention to methodological consistency makes it difficult to integrate the research to date into a clear picture of what is known and not known about the effects of toxic substances on human behavior. In view of the variation in methods of subject selection, measurement, and statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…It accumulates in the brain even at low concentrations that are present in the environment [43]. It is retained in the brain for long periods of time even after external exposure ceases and blood Pb levels decline.…”
Section: Discussionmentioning
confidence: 99%
“…It accumulates in the brain even at low concentrations that are present in the environment [43]. It is retained in the brain for long periods of time even after external exposure ceases and blood Pb levels decline.…”
Section: Discussionmentioning
confidence: 99%
“…Selected key features of studies included in five reviews of lead and cognitive function in adults, 1990-2007. Included in reviews? Study Ehle, 1990 Balbus, 1995 Morgan, 1974, Repko, 1975, Repko, 1977, and Repko, 1978 (Focused on exposed versus non-exposed comparisons but blood lead not measured in 'controls') Ahmed, 1987(Ahmed et al, 1987 Maizlish, 1995(Maizlish et al, 1995 …”
Section: Results In Question and Answer Formatmentioning
confidence: 99%
“…We relied on five previous reviews of the cognitive effects of lead in adults (Balbus-Kornfeld, Ehle and McKee, 1990;Goodman et al, 2002;Meyer-Baron and Seeber, 2000;Shih, Hu, Weisskopf, & Schwartz, 2007) supplemented by PUBMED searches and crosschecking of references to ascertain whether any relevant papers had been missed. We cite all English language publications on adult lead exposure and cognitive function, but limit our more detailed review to recent studies that measured lead dose by both blood lead and bone lead, for reasons that will be discussed in detail below.…”
Section: Methodsmentioning
confidence: 99%
“…The investigators concluded that "the methodologies in the studies reviewed were so varied and the cultures in which the studies were conducted so diverse that it is impossible to generalize across findings." However, Ehle and McKee (1990) found some evidence that increased irritability and fatigue may lead to interpersonal problems.…”
Section: Health Effectsmentioning
confidence: 99%
“…Current PbB as well as a TWA may have lacked the sensitivity to detect the decrement in performance. Ehle and McKee (1990) reviewed the methodology and conclusions of 14 published reports to determine if any consensus regarding neurobehavioral effects of low-level lead exposure in adults could be reached.…”
Section: Health Effectsmentioning
confidence: 99%